Therapy-resistant autoimmune nodopathy with anti-neurofascin 155 antibodies: a case report - Teodors Talers; Daina Pastare; Daina Pastare; Guntis Karelis; Guntis Karelis; Eva Sankova (Frontiers in Human Neuroscience, 2024)
This study reports the case of a previously healthy man in his late 20s who began experiencing symptoms 3 months before admission to our hospital, including arm and leg weakness and distal hypesthesia. Initially, the patient responded to corticosteroid therapy. However, as his symptoms progressed, he underwent plasmapheresis and received intravenous immunoglobulin therapy, neither of which led to any discernible improvement. With rapid symptom progression during subsequent hospital visits, further investigation led to the detection of neurofascin 155 antibodies. Based on existing evidence of its efficacy, rituximab treatment was initiated. To date, the patient has received three doses of rituximab, which has been partially ineffective. Thus, treatment is ongoing and includes a combination of rituximab and subcutaneous immunoglobulin.